Fiscal Policy in a Neo-Classical Growth Model: An Analysis of Time Required for Equilibrating Adjustment - Sato, Ryuzo (Review of Economic Studies, 1963)
Journal Article Fiscal Policy in a Neo-Classical Growth Model: An Analysis of Time Required for Equilibrating Adjustment Get access Ryuzo Sato Ryuzo Sato Honolulu, Hawaii Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 30, Issue 1, February 1963, Pages 16–23, https://doi.org/10.2307/2296026 Published: 01 February 1963